2017
DOI: 10.1016/j.psyneuen.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Defensive freezing links Hypothalamic-Pituitary-Adrenal-axis activity and internalizing symptoms in humans

Abstract: The Hypothalamic-Pituitary-Adrenal (HPA)-axis plays an important role in the expression of defensive freezing. Adaptive freezing reactivity, characterized by an immediate increase in acute stress and timely termination upon threat offset or need to act, is essential for adequate stress coping. Blunted HPA-axis activity in animals is associated with blunted freezing reactivity and internalizing symptoms. Despite their potential relevance, it remains unknown whether these mechanisms apply to humans and human psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
2
27
1
Order By: Relevance
“…Indeed, an ~threefold increase in CNTF levels was observed 20 min after acute stress in liquor collected from the 4 th ventricle (59.04 ± 26.41 pg/ml in control vs. 220.27 ± 98.51 in stress, *P  <   0.05; Fig 2E). Acute stress invariably evokes characteristic defensive behaviors, with an initial period of immobility (“freezing”) followed by hypolocomotion (Morilak et al , 2005; de Andrade et al , 2012; Niermann et al , 2017) used as key indicators. If CNTF volume transmission mediates acute stress responses, then CNTF infusion into the cerebrospinal fluid under ambient conditions ought to mimic stress‐induced behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, an ~threefold increase in CNTF levels was observed 20 min after acute stress in liquor collected from the 4 th ventricle (59.04 ± 26.41 pg/ml in control vs. 220.27 ± 98.51 in stress, *P  <   0.05; Fig 2E). Acute stress invariably evokes characteristic defensive behaviors, with an initial period of immobility (“freezing”) followed by hypolocomotion (Morilak et al , 2005; de Andrade et al , 2012; Niermann et al , 2017) used as key indicators. If CNTF volume transmission mediates acute stress responses, then CNTF infusion into the cerebrospinal fluid under ambient conditions ought to mimic stress‐induced behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in this basic defensive stress reaction have been linked to long‐lasting internalizing symptoms (i.e., signs of anxiety and depression) in animals (Kalin & Shelton, ; Qi et al., ). Recent cross‐sectional studies have confirmed the association between prolonged freezing and internalizing symptoms in humans (Kozlowska et al., ; Niermann et al., ). Although objective, early life risk markers are needed, the predictive value of early alterations in freezing for the later development of internalizing symptoms is not known.…”
Section: Introductionmentioning
confidence: 84%
“…& Dickerson, 2012), and in predicting psychopathology (Niermann et al, 2017). Hence, we include studies examining both reactivity and recovery phases of the stress response.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Stress researchers generally refer to the initial activation of the acute stress response as “reactivity,” and quantify the size of the reactivity response as the change from baseline to peak levels of neuroendocrine hormones such as alpha‐amylase (SAM) or cortisol (HPA). The post‐stressor deactivation and restoration phase, conceptualized as the efficiency or rapidity with which an individual's hormones return to baseline levels following the peak, is referred to as “recovery.” Distinguishing between reactivity and recovery is important because examination of the reactivity and recovery phases separately has proven helpful in specifying outcomes of different coping behaviors (e.g., Wadsworth et al, ; Zoccola & Dickerson, ), and in predicting psychopathology (Niermann et al, ). Hence, we include studies examining both reactivity and recovery phases of the stress response.…”
Section: Introductionmentioning
confidence: 99%